Score cardiovascular fetal e índice de performance miocárdica na predição de resultados neonatais em fetos com crescimento intrauterino restrito acompanhados no Hospital das Clínicas da UFMG em 2022 - Rayra Amana Macêdo Maciel (2024)
OBJECTIVE: To assess whether fetal cardiovascular score and myocardial performance index (MPI) are associated with worse neonatal outcomes in fetuses diagnosed with intrauterine growth restriction (IUGR) followed at the Clinics Hospital of UFMG in 2022. METHODOLOGY: This is a prospective and longitudinal study that included patients followed at the high-risk prenatal care at the Clinics Hospital of UFMG for IUGR. The fetuses were monitored with Doppler velocimetry, and the timing of delivery was guided according to institutional protocol. Fetal cardiac function was evaluated using the fetal cardiovascular score and MPI, and perinatal outcomes were assessed. Statistical association tests included calculation of Odds Ratio (OR), Fisher's Exact test, Student's t, and Pearson's correlation test. RESULTS: No statistically significant differences were observed in the analysis between late and early IUGR fetuses, even in the isolated analysis of E/A ratio values. Considering the overall sample, an association was identified between an increased risk of death for cases where there were alterations in the percentile of umbilical artery Doppler, Fetal Cardiovascular Score, and Ductus Venosus. Associations were also observed between the outcome of death and lower mean CPR percentiles, lower ICT values, lower gestational ages at birth, as well as associations with higher mean percentiles of uterine artery Doppler and TE values. An association was also identified between neonatal death and alteration of MPI parameters, as well as the correlation of this and lower Apgar scores at 5 minutes. CONCLUSION: The parameters of fetal cardiovascular score and myocardial performance index, as well as alterations in fetal Doppler velocimetry, are associated with worse neonatal outcomes. No statistically significant differences were found between late or early IUGR.